Histopathological Changes of the Effect of Ketotifen in a Rat Model of Nephropathy - Shaza Anwar Al Laham (Journal of Pharmacy and Nutrition Sciences, 2019)
Acute kidney injury (AKI) remains a common clinical problem with serious consequences and unsatisfactory therapeutic options. Mast cells are distributed in the kidneys, have a role in the inflammation. Thus, a model of Acute kidney injury of rhabdomyolysis induced by glycerol was done in order to investigate the possible healing effect of Ketotifen, a selective stabilizer of mast cells and a histamine H1 receptor antagonist, in rats. Methods: Wister rats (250-350 g) were used. Renal failure was produced by rats deprived of water for 24 hours followed by i.m. injection with 50% (vol/vol) glycerol (10 ml/kg of body weight). After 30 min, Ketotifen was used at a dose of 2 mg/kg. Rats received treatment for 5 consecutive days. On the 6th day, the rats were sacrificed; blood was obtained for blood urea and creatinine assays. The kidney tissue was used for the determination the histological injury. Results: The levels of urea and creatinine were decreased significantly (